SOPs and improving business performance to meet GXP - Winning, Richard (Henry Stewart Talks, 2013)
The basics of process mapping for business use, How process maps can be used to deliver useful and effective SOPs and procedural information, How process maps can be linked in a hierarchical way to provide the basis of an organised SOP /procedural management system, The importance and use of best practice standards to underpin process maps for SOPs, The use of Enterprise Architecture applications to create and store process maps and to enable business analysis and process modelling